Pengaruh Struktur Modal Terhadap Nilai Perusahaan Dengan Profotabilitas Sebagai Variabel Moderasi - Umi Rahma Dhany; Wilamsari, Feni; Ahmad Iskandar Rahmansyah; Titik Musriati (Institut Teknologi dan Sains Mandala, 2024)
In the midst of the increasingly rapid development of the business world, company value plays an important role, especially in the eyes of investors. Company value is an important element that describes the success of achieving company performance. There are several factors that can influence company value, including capital structure and profitability. This research aims to examine the effect of capital structure on company value with profitability as a moderating variable. In this case, capital structure is proxied by the Debt Equity Ratio (DER), while company value and profitability are proxied by the Price Earning Ratio (PER) and Return on Equity (ROE), respectively. The object of this research uses a sample of government-owned commercial banking companies listed on the Indonesia Stock Exchange (BEI) during the observation period 2016 - 2023. The sample was selected based on predetermined criteria and data analysis using Smart PLS3. The results of hypothesis testing show that the DER variable has no effect on PER in government-owned commercial banking companies, while ROE is able to moderate the effect of DER on PER in government-owned commercial banking companies.